Achmatowicz rearrangement-enabled unified total syntheses of (+)-passifetilactones A-C - Verma, Aman Kumar; Jeddi, Dharmaraju; Kontham, Ravindar (RSC Advances, 2025)
In this manuscript, we report the enantio- and diastereoselective total synthesis of three cytotoxic 2-pyrone-derived natural products passifetilactones A-C. Our strategy leverages a unified synthetic approach that originates from simple furan-based building blocks. Key transformations include the Corey-Bakshi-Shibata (CBS) reduction to access chiral furan-derived alcohol, NBS-mediated Achmatowicz rearrangement to construct the alpha-hydroxy-delta-pyrone core, followed by a highly stereoselective, iridium-catalyzed dynamic kinetic intramolecular redox isomerization to access the delta-hydroxy-alpha-pyrone framework. This streamlined route enables efficient access to passifetilactones A, B, and C in 13, 5, and 8 steps, with overall yields of 12%, 54%, and 37%, respectively.